Spectroscopic study of methylene blue in vivo: effects on tissue oxygenation and tumor metabolism - D. V. Pominova; A. V. Ryabova; A. S. Skobeltsin; I. V. Markova; I. D. Romanishkin; V. B. Loschenov (Biomedical Photonics)
Methylene blue (MB) is a promising photosensitizer (PS) for the treatment of pathological neoplasms, since it has both photodynamic activity (under laser irradiation) and redox and catalytic properties (in the absence of light). In the framework of this work, using spectroscopic methods, the effect of intravenous administration of MB on tissue oxygenation of hemoglobin in small animals in vivo in tumor and normal tissues was analyzed. The influence of MB on cell metabolism was analyzed. It has been shown that the use of MB promotes an increase in oxygen consumption by the tumor, and also leads to a shift in metabolism towards oxidative phosphorylation. It was shown that the use of MB contributes to an increase in oxygen consumption by the tumor, and also leads to a shift in metabolism towards oxidative phosphorylation.